Level of Students’ Satisfaction with the Academic Environment in a Nursing Campus - Singh, Ajanta Maharjan; Dhakal, Sushma (Interdisciplinary Research in Education, 2025)
Introduction: The academic environment refers to the educational setting of the classroom, encompassing quality teaching, collaboration and teamwork, access to learning facilities, and administrative support. A supportive academic environment can help nursing students achieve higher academic performance and a higher level of satisfaction. Students' satisfaction with the academic climate means the feeling of happiness and fulfilment experienced in the educational environment of their institution. Students’ satisfaction can be the basis for identifying the areas that need improvement in the academic environment, leading to better learning experiences. The main objective of this study was to determine the students’ satisfaction with the academic environment in a nursing campus.Methods: A descriptive cross-sectional design was used to find out students’ satisfaction with the academic environment in a nursing campus. Maharajgunj Nursing Campus was the study setting. The study population consisted of all bachelor-level nursing students. The census method was used to collect the samples. The total sample size was 238.  A self-administered questionnaire consisting of 40 items with a Likert Scale (1-5) was used to collect the data. The collected data were analysed using descriptive and inferential statistics.Results: The study shows that 89.5% of the nursing students were highly satisfied with the academic environment, while 10.5% were least satisfied. The study also reveals that students’ level of satisfaction with the academic environment was significantly associated with age (p=0.036) and academic year(p=0.044).Conclusion: Most of the students are highly satisfied with the academic environment, basically with the quality of teaching. However, they are less satisfied with the support system during stress, channels for expressing their complaints, and administrative support. A student's counselling and support system needs to be enhanced for a better learning environment.